A case of acute myocardial infarction in a working-age patient with ulcerative colitis against the background of late initiation of pathogenetic therapy - Larisa V. Tarasova; Nadezhda Yu. Kucherova; Julia V. Tsyganova (LLC "MEDIAFORMAT", 2023)
The article describes a case of acute myocardial infarction with multiple atherosclerotic lesions of the coronary arteries in a working-age patient with ulcerative colitis, against of late initiation of pathogenetic therapy.